ANALISIS KEPUASAN PELANGGAN MELALUI KUALITAS PRODUK DAN BAURAN PEMASARAN AMARTA LOUNGE DI HOTEL SANTIKA PREMIERE SEMARANG - Wijoyo, Tuwuh Adhistyo; Prasetyo, Danang Mursid (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The objective of this investigation is to assess and scrutinize the manner in which consumers comprehend the caliber of the commodities they acquire, as well as the impact exerted by the marketing mix, comprising elements like product, price, place, promotion, people, physical evidence, and process, on the degree of customer contentment.This study was conducted at Amarta Lounge in Hotel Santika Premiere Semarang with the aim of evaluating and explaining the influence of service quality and marketing mix on customer satisfaction. Amarta Lounge in Hotel Santika Premiere Semarang has poor service quality and marketing mix, which negatively impacts customer satisfaction. Research data were collected through questionnaires, involving 96 respondents. The results of the study are expected to assist both management and customers. Service quality and marketing mix have a significant influence on customer satisfaction. Multiple regression analysis results show the influence of independent variables on the dependent variable, hypothesis testing, and validity and reliability tests. Quantitative analysis using multiple regression analysis was employed to determine the influence of independent variables on the dependent variable. This indicates that a good marketing mix and service quality are necessary to enhance customer satisfaction